Asia Pacific Education Diversity, Challenges and Changes - Chan, Philip Wing Keung (Education, 2012)
Education in Asia Pacific countries is being transformed by globalisation and the market economy. Most economies within the region have flourished due to increased regional capital flow, trade and other forms of economic and political interaction. The Asia Pacific also has rich and unique traditions, which create cultural diversity as well as common challenges, including obstacles of language and geographical separation. Additionally, there is a growing reaction to the predominance of Western social theories that is fuelling recognition of and movement towards theories that reference the wide range of contextual and cultural perspectives available in the East. Contributors offer Eastern-oriented perspectives on teacher education, parent participation, government withdrawal, textbook content, uses of modern technology, the challenges of migrating families and tertiary students who travel from overseas for study. Their commentaries highlight issues of equity, identity and social justice.